Proyecto de Empresa Abuelo 911 - Lara Grados, Jose Humberto (2021)
In 2020, with the pandemic caused by Covid 19, represented health challenges, revalued the importance of the family, demolished the paradigms of telework, accelerated the Digital Transformation with the exponential growth of Electronic Commerce due to the use of applications such as Uber, Rappi and others that were positioned since 2009. "The New Normal" generated change in the business models of current companies and gave strength to businesses provided from digital platforms in the market in which we must establish ourselves. The objective of this thesis is to test the feasibility of the Abuelo 911 project, which was born with the proposal to cover the services required by the accelerated rhythm of life of people between 25 and 55 years of age of the NSE A and B of the homes of Modern Lima, who demand help in various domestic tasks such as: tutoring, cooking, painting, etc. Abuelo 911 provides these services with Older Adults who are knowledgeable about these matters, with the warmth that characterizes them through a digital platform that will consolidate the services in an agile, friendly and immediate way. And this is the differential factor of Abuelo 911, which indirectly contributes to improving the quality of life of the Elderly, being the strategic partner in whom young people find the wisdom and confidence they need in their home according to the interviews. SEO / SEM strategies, Google analytics will be used to properly manage market capture and consumption frequency. An estimated 5 765 services and customer acquisition of 40% for the first year, reaching the fifth year with 21 739 services. Abuelo 911 will invest S/ 54 951 with an IRR of 69,6% being viable from the financial and commercial aspect with the acceptance of the target audience that values the proposal for having the social and technological impact that differs from the competition.